Evaluasi Program Magang dengan Model Evaluasi Kirkpatrick - Suparno, Suparno; Sirajuddin, Sirajuddin; Zulkarnain S, Zulkarnain S; Suradi, A (JOEAI (Journal of Education and Instruction), 2023)
This study aims to assess the evaluation of apprenticeship programs using the Kirkpatrick evaluation model at PT Jambi Prima Coal. This study used a quantitative method with a gradual pre- and post-test evaluation approach to apprentice participants at four levels, namely 1) the level of satisfaction of the participants with the implementation of the training, as measured by a questionnaire for the participants; 2) the participants' level of understanding of the training material, as measured by the pre-test and post-test questions for the participants; 3) changes in the work behavior of the training participants after returning to work, as measured by a questionnaire for the participants' superiors and subordinates; 4) the impact of changes in the work behavior of the training participants on the company's productivity level, as measured by the reduction in waste due to decreased absenteeism and tardiness of staff led by the training participants. The first three levels of data are processed using Kirkpatrick's weighting formula. The results of the evaluation show that the satisfaction level of the participants ranges from 77-83%. The pre-test average value was 46.58%, while the post-test average value was 58.50%. Of the 20 participants, 16 people had better work behavior according to their superiors, and all of them according to their subordinates. The data shows that there is no decrease in the lateness rate but there is a decrease in the absenteeism rate. In conclusion, the satisfaction level of the training participants showed a positive reaction, most of the participants showed an increase in understanding of the material, most of the training participants were quite able to apply the training material well in the workplace and there was a decrease in absenteeism which had an impact on saving the company. Keywords: Training, Apprentice Evaluation, Kitkpatrick Model